The relationship between the gut microbiota of eight dung beetle species (Coleoptera: Scarabaeidae: Scarabaeinae) and their feeding orientations - Sole, Catherine, L (University of Pretoria, 2023)
Dissertation (MSc (Entomology))--University of Pretoria, 2023.